The Effects of Corporate Image, User Image, and Product Image Towards Purchasing Interest of Suzuki Motorcycle - Rahayu, F A; ., Fitriana; Zanky, M N (KnE Social Sciences, 2018)
Recently, motorcycle and automotive industry is having a good development in Indonesia. The motorcycle market in Indonesia is still big, because not only facilitating people’s activities, but also the price is still rational. That makes the competition in motorcycle and automotive industry become tighter. There are major companies that dictate the Indonesian market, one of them is Suzuki. Suzuki is a corporate which is annually trusted by consumers and also making some innovations toward its products to upgrade the qualities. This study aims to know the variable effect of corporate image, user image, and product image towards interest of purchasing Suzuki motorcycle. The population of this study is students of Management Department batch 2014-2015, Faculty of Economics in Universitas Negeri Malang, East Java, Indonesia who use Suzuki motorcycle. The sample of this study is 115 respondents. The sampling technique is using proportional random sampling and the data analysis is using statistical descriptive and multiple regression analysis. The result shows that corporate image, user image, and product image positively and significantly affect the interest of purchasing Suzuki motorcycle. The result can be proposed as an input for management party to boost consumer interests. Keywords: corporate image, user image, product image, purchasing interest